MENINGKATKAN MINAT DAN PRESTASI BELAJAR MATEMATIKA DENGAN MODEL PEMBELAJARAN GROUP INVESTIGATION SISWA KELAS VII A SMP NEGERI 1 POLANHARJO KLATEN - Takdir Sukmo Wijayanti; Esti Harini (Universitas Sarjanawiyata Tamansiswa, 2014)
This research aimed to increase the interest mathematics learning and student achievement of class VII A SMP N 1 Polanharjo used to cooperative learning Group Investigation (GI) type. The types of research was Classroom Action Research (CAR). Research was conducted minimal two cycles actions. Data was collected by observation, questionnaires, tests and documentation. Results showed an increase student interests viewed from observation and questionnaire. Student achievement increased to by 52.56 at pre-cycle to 63.48 in cycle I and increased to 66.54 in cycle II. Therefore suggested to teachers use the GI type to increase student interest and achievement.